Lowering blood sugar levels with kersen leaf stew (muntingia calabura l) and black onion (alium sativum) extract in mice (mus musculus) - Sumarliyah, Eni; Nasrullah, Dede; ., Sukadiono; Pankyano, Desta (International Journal of Advanced Nursing Studies, 2020)
Diabetes mellitus (DM) is a metabolic disease characterized by an increase in blood sugar levels. Blood sugar levels in patients with DM are mostly challenging to control, and this will threaten the occurrence of complications. Alternative therapies used are active flavonoids in reducing blood glucose. The purpose of this study was to analyze the decrease in blood sugar levels by administering cherry leaves stew and black onions to mice (mus musculus). The design of this study was the Quasy Experimental design (pretest-posttest with control group design). The sample in this study was 32 mice, 16 in the intervention group, and 16 comparison groups. There are independent variables (Kersen Leaf Stew and Black Onion Extract) and the dependent variable (Blood Glucose Level). The data were collected using an observation sheet, then analyzed using the independent sample T-test and Kolmogorov Smirnov test. The results of this study showed that the pre and post administration of cherry leaf decoction was 36.5 mg/dl, and the difference between pre and post administration of black onion extract was 24.3 mg/dl. While the analysis showed p = value 0.98, it showed no difference in the effectiveness of the two extracts in reducing blood sugar levels in mice. Obtained comparative test results from the two extracts were equally effective in lowering blood sugar in mice. Thus further research needs to be done with more samples.Â Â